Experiencias de investigación en la secundaria: una visión desde adentro - D’Antoni, Maurizia (2010)
This paper shows results of the project on Alfabetización crítica en la cultura escolar: Cultura política en la educación secundaria costarricense, currently being developed at the División de  Educología, Universidad Nacional, Costa Rica. The first phase of this research refers to the aim to know more about the reaction of high school students dealing in the traditional authoritarian type school. There are evidences that a repressive and excluding scholar institution does not promote the integral development of the students. This new phase of the project gathers also the voice of teachers. Through the action-research methodology teachers are accompanied and encouraged into a process of deep thinking on those problematic aspects of the school environment. Our main objective is to compare the opinions between students and teachers. experiencias de investigación en la secundaria: una visión desde adentro